Lipid droplet‐dependent fatty acid metabolism controls the immune suppressive phenotype of tumor‐associated macrophages. Issue 11 (10th October 2019) - Wu, Hao; Han, Yijie; Rodriguez Sillke, Yasmina; Deng, Hongzhang; Siddiqui, Sophiya; Treese, Christoph; Schmidt, Franziska; Friedrich, Marie; Keye, Jacqueline; Wan, Jiajia; Qin, Yue; Kühl, Anja A; et al.
Abstract: Tumor‐associated macrophages (TAMs) promote tumor growth and metastasis by suppressing tumor immune surveillance. Herein, we provide evidence that the immunosuppressive phenotype of TAMs is controlled by long‐chain fatty acid metabolism, specifically unsaturated fatty acids, here exemplified by oleate. Consequently, en‐route enriched lipid droplets were identified as essential organelles, which represent effective targets for chemical inhibitors to block in vitro polarization of TAMs and tumor growth in vivo . In line, analysis of human tumors revealed that myeloid cells infiltrating colon cancer but not gastric cancer tissue indeed accumulate lipid droplets. Mechanistically, our data indicate that oleate‐induced polarization of myeloid cells depends on the mammalian target of the rapamycin pathway. Thus, our findings reveal an alternative therapeutic strategy by targeting the pro‐tumoral myeloid cells on a metabolic level. Synopsis: Tumor‐associated macrophages (TAMs) are the main regulatory cell type in the tumor stroma as well as the microenvironment. This study describes how fatty acids polarize myeloid cells to TAMs and how this polarization is controlled by lipid droplet‐dependent fatty acid metabolism. The fatty acid‐enriched tumor environment itself was sufficient to induce the regulatory phenotype of TAMs, including the up‐regulation of classical markers like CD206, IL‐6, VEGFα, MMP9 or Arg1. The fatty acid‐induced TAM polarization was lipid droplet dependent. mTORC2 activation played a critical role in the generation of the suppressive myeloid cell phenotype. Cell‐specific inhibition of DGAT1 and 2 prevented oleate‐induced polarization into immunosuppressive TAMs in vitro in murine and human cell culture systems as well as in vivo in a murine tumor model. Abstract : Tumor‐associated macrophages (TAMs) are the main regulatory cell type in the tumor stroma as well as the microenvironment. This study describes how fatty acids polarize myeloid cells to TAMs and how this polarization is controlled by lipid droplet‐dependent fatty acid metabolism.